Hydrologic analysis of the Yellow River based on linear regression and M-K mutation test - Chen, Mingyi (Transactions on Environment, Energy and Earth Sciences, 2024)
Hydrological analysis of the Yellow River is of great significance to alleviating soil erosion of the Yellow River. In order to better analyze the relationship between water level, water flow and sediment content of the Yellow River downstream of the Xiaolangdi reservoir, based on linear regression and Mann-Kendall mutation test, combined with the advantages of Zhang et al. in handling with linear regression and M-K mutation test, a linear regression fitting model and M-K mutation test model for hydrological analysis are constructed. Considering from both micro and macro perspectives, this article obtained linear relationships between the water level, water flow and sediment content of the Yellow River, and them correspond mutations time. The accuracy of these analysis has important reference value for sediment regulation, flood control and alleviation of soil erosion, then disaster prevention.